Disaster Mitigation as a Non-Traditional Security Strategy: Evidence from Local Resilience Initiatives in Indonesia - Putri Maulidiah; Berton SP Panjaitan; Sugimin Pranoto (International Journal of Education, Vocational and Social Science, 2026)
This study examines disaster mitigation as a non-traditional security strategy by analyzing its role in strengthening local resilience and contributing to national stability in Indonesia. As a disaster-prone country located in the Pacific Ring of Fire, Indonesia faces multidimensional risks that not only affect physical infrastructure but also threaten social and political stability. This research employs a qualitative literature review approach, drawing on policy documents, academic publications, and reports related to disaster risk reduction and local governance. The findings indicate that disaster mitigation at the local level, particularly through community-based and government-led initiatives, plays a strategic role in enhancing resilience, reducing vulnerabilities, and supporting national security. However, challenges such as limited resources, weak institutional coordination, and low community awareness hinder effective implementation. Strengthening local governance capacity, promoting multi-stakeholder collaboration, and integrating local knowledge into disaster management are essential strategies to optimize mitigation efforts. This study contributes to the discourse on non-traditional security by positioning disaster mitigation as a critical component of national stability.